Design, synthesis and antimicrobial activity of 6-N-substituted chitosan derivatives. Issue 18 (15th September 2016) - Hu, Linfeng; Meng, Xiangtao; Xing, Ronge; Liu, Song; Chen, Xiaolin; Qin, Yukun; Yu, Huahua; Li, Pengcheng
Graphical abstract: Abstract: Three novel 6- N -substituted chitosan derivatives were designed and synthesised and characterized by FTIR and NMR. The degree of substitution was calculated by elemental analysis results. The antimicrobial activities of the target compounds were evaluated by twofold serial broth dilution method and poisoned food technique. The antifungal activities of 6-aminoethylamino-6-deoxy chitosan (3 ), 6-butylamino-6-deoxy chitosan (4 ) and 6-pyridyl-6-deoxy chitosan (5 ) were significantly increased against Rhizoctonia cerealis, Fusarium oxysporum and Botrytis cinerea, and the inhibition rate ranged from 22.48% to 63.56% at the concentration of 0.2 mg/mL. The compound3 had better antibacterial activities than chitosan, and the minimum inhibition concentration of which ranged between 6.25 and 25 mg/L against gram-positive bacteria ( Staphylococcus aureus, Bacillus subtilis and Bacillus anthracis ) and gram-negative bacteria ( Escherichia coli, Salmonella typhi ). The antibacterial activities of 6- N -substituted chitosan tended to increase with the increase of the number of –NH2 group.